Deteksi Pengendalian Internal SIA Pengeluaran Kas Pada Usaha Stockist Melalui Audit Kepatuhan - Mei Nurlinda; Siti Maisyaroh; Tri Ratnawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to analyze the systems and procedures for disbursing cash in the stockist business regarding the suitability of the performance procedure system, as well as implementing strong internal controls so as to benefit from the implementation of compliance audits in the internal control of cash disbursements, such as increasing the effectiveness and efficiency of the cash purchase process, reducing the risk abuse and fraud, as well as increasing accountability and transparency in the management of funds. By using the basis of theories about systems and procedures, compliance audits, and internal control of cash disbursements, as well as qualitative descriptive methods based on primary data collected from interviews and observations. Data analysis will involve categorizing and finding patterns or themes that emerge from the data. The result of the research is that the stockist business flowchart systems and procedures show weak internal controls, due to not implementing supporting document verification, transaction security, as well as employee training and awareness. So that it can beupdated by adding IT, accounting, and internal audit, as well as implementing compliance auditing and internal control.